Comportamento hidrossedimentológico de uma bacia hidrográfica rural utilizando técnicas de monitoramento e modelagem - Barros, Claudia Alessandra Peixoto de (2012)
The aim of this study was to analyze the hydrological behavior of a watershed with intense agricultural activity based on rainfall, water discharge and suspended sediment concentration data. The study provides an analysis based on monitoring and modeling techniques with special emphasis to the water infiltration estimate at catchment scale, the runoff modeling and processes of suspended sediment transfer from hillslopes to fluvial channel. The experimental catchment is located in the central-north part of Rio Grande do Sul State, Brazil, with a drainage area of 1.19 km2, which is characterized by shallow soils, steep hillslopes, tobacco cultivation and high sediment yield. Besides the daily and monthly data, the study focuses on 77 rainfall-runoff-sediment events from September 2009 to August 2011. For this data series were used three different models, they being the infiltration model based on hietogramas and hydrographs analysis, curve number model and LISEM model, both with analysis on the estimate infiltration and the runoff. The obtained result for this watershed indicated that: a) the empirical and simple model for infiltration and surface runoff estimation had a fine adjustment with the observed data from the hietograms and hydrograms, b) LISEM model calibration was able to describe the spatial and temporal infiltration variability and surface runoff in a watershed scale. These results contribute for a better understanding of hidrosedimentological processes in a watershed scale, indicating that the use of erosion and sediment yield mathematical modeling tools is efficient for practical indications of soil use and management for reducing environmental and economical problems resulted from runoff and erosion.